2020
DOI: 10.1111/tbed.13871
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sero‐prevalence of brucellosis in small ruminants of India: Nationwide cross‐sectional study for the year 2017–2018

Abstract: Brucellosis in small ruminants caused mainly due to Brucella melitensis is an important zoonotic disease characterized by abortion, retained placenta, infertility, orchitis, epididymitis and rarely arthritis. Small ruminants are the main source of economy for the rural and marginally poor farmers and brucellosis is resulting in huge economic losses due to abortions and infertility and causing public health concern among the small ruminant keepers. Bovine brucellosis control programme has been implemented in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It was also revealed that difference in prevalence of brucellosis was nonsignificant between sheep and goat populations. Similar to our findings, Shome et al [ 9 ] also reported an apparent prevalence of 7.45% in small ruminants of our neighboring country, India, but contrary to our findings, they recorded significantly higher prevalence in sheep as compared to goats ( p < 0.0001). In contrast to our findings, some previous studies showed lower prevalence rates of small ruminant brucellosis such as 1.79% in Tselemti district, Northern Ethiopia [ 45 ], 1.8% in Debre Zeit and Modjo export abattoirs of Oromia Regional State of Ethiopia [ 46 ], 1.2% in Gambia [ 47 ], 5.1% in different farms of Punjab, Pakistan [ 36 ], 6.26% in Southeast Europe [ 48 ], 0.4% in Northwest Ethiopia [ 49 ], 3.4% in Quetta and its surrounding areas of Pakistan [ 50 ], 3.2% in Borena, Southern Ethiopia [ 51 ], and 4.5% in China [ 52 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was also revealed that difference in prevalence of brucellosis was nonsignificant between sheep and goat populations. Similar to our findings, Shome et al [ 9 ] also reported an apparent prevalence of 7.45% in small ruminants of our neighboring country, India, but contrary to our findings, they recorded significantly higher prevalence in sheep as compared to goats ( p < 0.0001). In contrast to our findings, some previous studies showed lower prevalence rates of small ruminant brucellosis such as 1.79% in Tselemti district, Northern Ethiopia [ 45 ], 1.8% in Debre Zeit and Modjo export abattoirs of Oromia Regional State of Ethiopia [ 46 ], 1.2% in Gambia [ 47 ], 5.1% in different farms of Punjab, Pakistan [ 36 ], 6.26% in Southeast Europe [ 48 ], 0.4% in Northwest Ethiopia [ 49 ], 3.4% in Quetta and its surrounding areas of Pakistan [ 50 ], 3.2% in Borena, Southern Ethiopia [ 51 ], and 4.5% in China [ 52 ].…”
Section: Discussionsupporting
confidence: 79%
“…In rare cases, it may also cause arthritis in small ruminants [ 41 ]. It has worldwide distribution and is endemic in many developing/underdeveloped countries including Pakistan [ 9 , 42 ]. In most of the developing countries like Pakistan, the small ruminants and their products play an important role in the national economy and also support millions of people living in rural and urban areas as the source of meat, milk, cheese, cream, yogurt, hooves, horns, and leather [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis caused by B. melitensis is one of the major zoonotic disease worldwide; hence, it requires early diagnosis and control. Brucellosis is endemic in India, and a nationwide survey (24,056 small ruminants tested) showed that there was an 11.55% sero-prevalence of brucellosis in sheep, while there was 5.37% sero-prevalence in goats ( Shome et al, 2020 ). The bacterial strain used in the present study (TN_CUL_1) was isolated from a sheep from Tamil Nadu, India.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the seroprevalence and spatial distribution of Brucella in small ruminants, a nationwide seroscreening for brucellosis was conducted during 2017-2018. Using indirect ELISA, the overall apparent and true prevalence of brucellosis was 7.45 per cent [95% confidence interval (CI): 7.13-7.79] and 3.79 per cent (95% CI: 3.44-4.17), respectively, in small ruminants 16 .…”
Section: Surveillance Activities For Major Zoonotic Diseases and Antimicrobial Resistancementioning
confidence: 99%